2020
DOI: 10.1161/jaha.119.015490
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome and Ischemic Heart Disease in Pregnancy: Data From the EURObservational Research Programme‐European Society of Cardiology Registry of Pregnancy and Cardiac Disease

Abstract: Background The prevalence of ischemic heart disease (IHD) in women of child‐bearing age is rising. Data on pregnancies however are scarce. The objective is to describe the pregnancy outcomes in these women. Methods and Results The European Society of Cardiology‐EURObservational Research Programme ROPAC (Registry of Pregnancy and Cardiac Disease) is a prospective registry in which data on pregnancies in women with heart disease were collected from 138 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…This probably follows significant improvements in diagnosis and treatment over time and bias in collecting data mainly from severe or fatal cases in older reports. Accordingly, in the largest prospective study to date on pregnant women affected by acute coronary syndromes, no maternal deaths were recorded [ 35 ]. In line with this result, another recent study observed comparable rates of in-hospital mortality after AMI between pregnant women and the general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This probably follows significant improvements in diagnosis and treatment over time and bias in collecting data mainly from severe or fatal cases in older reports. Accordingly, in the largest prospective study to date on pregnant women affected by acute coronary syndromes, no maternal deaths were recorded [ 35 ]. In line with this result, another recent study observed comparable rates of in-hospital mortality after AMI between pregnant women and the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the recent literature suggests that rates of CS are notably higher in women with pregnancy-related AMI, more than twice those in healthy women in Europe [ 35 , 72 ]. Indeed, CS appears to be the safest approach to delivery after an acute cardiac event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, more recent results from the large EURObservational Research Programme Registry of Pregnancy and Cardiac disease registry have added to our understanding of the maternal and fetal outcomes of women with different cardiac conditions, including women with uncorrected CHD, 15 transposition of great arteries, 16 aortic coarctation 17 and in those with ischaemic heart disease. 18 Most of these studies are predominantly from HIC, and many have focused on women with CHD 15-17 19-21 as well as in general CVDs. 2 3 18 22 23 Although the majority of studies have reported an increased risk of adverse maternal and fetal outcomes, 3 15 19 20 22-26 others did not show this increased risk.…”
Section: Open Accessmentioning
confidence: 99%
“…Profound physiological changes including significant hormonal, metabolic and haemodynamic shifts and their impact on cardiovascular and pulmonary systems during pregnancy are widely recognised. Studies have found that women with any history of pregnancy have increased long-term risk of hypertension,1 ischaemic heart disease (IHD),1 myocardial infarction (MI),2–4 ischaemic stroke and intracerebral haemorrhage,5–9 venous and arterial thromboembolism 10 11…”
Section: Introductionmentioning
confidence: 99%